Implementation of Problem-Based Learning to Improve Biology Learning Outcomes of Grade XI-D Students at MAN 1 Pamekasan - Sofyan Maulidi; Achmad Ali Fahmi; Moch Haikal; Linta Wafdan Hidayah; Husnol Khotimah (Lombok Institute, 2026)
This classroom action research aimed to improve the cognitive learning outcomes of Grade XI-D students at MAN 1 Pamekasan through the implementation of the Problem-Based Learning (PBL) model in Biology instruction. The study employed the Kemmis and McTaggart action research model in two cycles involving 26 students. The action focused on Biology topics with comparable cognitive demands, namely the immune system and the endocrine system. Data were collected through learning outcome tests, observation sheets, field notes, and documentation. The test consisted of items representing cognitive levels C1-C4 and was assessed using a scoring rubric. Quantitative data were analyzed using descriptive statistics, mastery percentages, a paired-sample t-test, and Cohen's d. The mean score increased from 67.8 in Cycle I to 80.4 in Cycle II, while mastery increased from 53.8% (14 students) to 88.5% (23 students). The paired-sample t-test showed a significant improvement, t(25) = 4.97, p < 0.001, with a large effect size (d = 0.974). Classroom observations indicated improved participation after clearer instructions, role distribution, teacher scaffolding, and better time management in Cycle II. These findings indicate that PBL can improve Biology learning outcomes and support active, collaborative learning.